Maternal Mortality and Preventive Measures among Childbearing Mothers in Abia State University Teaching Hospital - Ama, Abigail Eseni; John, Faith Asuquo; Mboho, Nsisong Ekom; Asuquo, Akanimo Okon; Udoaka, Etiene-Obong Johnson (PT. Riset Press International, 2025)
The study examined maternal mortality causes and preventive measures among childbearing mothers in Abia state university teaching hospital, Nigeria. Maternal mortality poses a threat to a population as it claims the lives of childbearing women who are wives, mothers, and caregivers amongst so many roles. Unfortunately, they die from preventable causes classified as direct obstetric and indirect obstetric causes. This trend is measured in various populations using the maternal mortality rate (MMR). The paper reviewed causes, risk factors and preventive measures of maternal mortality to modify the knowledge, attitude and practice (KAP) of childbearing women. The search strategy included a variety of key words on PubMed, Sciencedirect and other databases. In testing hypothesis, the results revealed a positive significant relationship of the stated preventive measures to maternal mortality causes. The study therefore recommends among others the need for health education to convince women of the relevance of seeking maternal care at the right time and in government approved health facilities.